Performance analysis of a single-wire capacitance sensor for interface level measurement in stratified multiphase flows. (June 2022) - Atkinson, Colin; Huang, Songming; Meredith, Andrew
Abstract: A single-wire capacitance sensor can be used to measure the interface level of a conductive liquid in a stratified multiphase flow. This type of capacitive sensor uses the conducting core in an insulated wire as its first electrode, and the conductive fluid as its second electrode, separated by the wire insulation, producing a coaxial capacitor with a variable electrode length linearly correlated to the liquid level. Therefore in theory, there should be a linear relationship between the liquid level and measured capacitance value. However, at low liquid levels, the authors have observed a noticeable departure from the theoretical correlation in the way of an upward offset. The cause for such a departure is investigated by means of a simplified model geometry and attributed to an additional capacitance between the wire conductor and conductive plane provided by the liquid interface. Analytical and numerical modelling have been carried out to better understand this effect. Recommendations are given on how to correct it. Highlights: A single-wire can provide a low-cost linear-response capacitive water level sensor. A stray capacitance forms between the water interface and the sensing wire. This stray capacitance causes an unwanted upward offset in sensor response. Analytical and numerical models have been developed to predict this error. Recommendations on how to correct this error under different circumstances.